Short Communication: Genetic diversity and phylogenetic analysis of two Indonesian local cattle breeds based on cytochrome b gene sequences - TETY HARTATIK; DWI NUR HAPPY HARIYONO; YUDI ADINATA (Society for Indonesian Biodiversity, 2019)
Hartatik T, Hariyono DNH, Adinata Y. 2019. Genetic diversity and phylogenetic analysis of two Indonesian local cattle breeds based on cytochrome b gene sequences. Biodiversitas 20: 17-22. Genetic diversity and phylogenetic relationships of two Indonesian local cattle breeds (Pasundan and Pacitan cattle) were investigated using mitochondrial DNA (mtDNA) cytochrome b (cyt b) gene analysis. Partial sequences of cyt b gene, 404 bp in length, were determined for 21 individuals from the two breeds. Genetic diversity of the breeds was assessed based on the number of polymorphic sites, number of haplotypes, haplotype diversity, nucleotide diversity and average number of differences. In addition, a neighbour-joining (NJ) haplotype tree was constructed based on Kimura’s two-parameter model. Among the two breeds, haplotype and nucleotide diversity of Pacitan cattle were the highest with values of 0.3778 and 0.00099, respectively. In contrast, Pasundan cattle had the lowest value for haplotype (0.1818) and nucleotide (0.00045) diversity. Four haplotypes (Hap_16, Hap_17, Hap_18 and Hap_19) were found across the two breeds and around 85.71% of investigated individuals were classified as Hap_16. Phylogenetic analysis with the inclusion of the cyt b sequences from 39 cattle breeds from Genbank database, showed that Indonesian cattle made a separated lineage together with Bos javanicus, B. bison, and B. bonasus. Pasundan and Pacitan cattle were considered from the same lineage based on haplotype distribution as well as phylogenetic analysis. This study may help the future researchers and livestock breeders for designing a breeding program based on a better understanding of the genetic diversity and history of local breeds.